Asymmetric light reflectance by Fano resonance between Fresnel reflection and localized surface plasmons. (30th July 2018) - Wang, He; Li, Penggang; Gao, Na; Huang, Kai; Kang, Junyong; Ji, Li; Yu, Edward
Abstract: The asymmetric light reflectance behavior arising from the Fano interference between Fresnel reflection and localized surface plasmons (LSPs) is investigated. Finite-difference time-domain (FDTD) simulation results demonstrate that, when light is incident from air, reflectance spectra show peaks at the LSP resonance wavelength regardless of the metal nanoparticle density. When light is incident from the substrate, reflectance spectra show typical Fano profiles. This phenomenon can be attributed to different reflectance phase shifts induced when light is incident from different directions. Experiments are conducted with Ag-nanoparticle-coated quartz wafers. The measured spectra are in good agreement with the simulated results.